2015
DOI: 10.1007/s10915-015-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional Optimal Error Estimates of BDF–Galerkin FEMs for Nonlinear Thermistor Equations

Abstract: In this paper we study linearized backward differential formula (BDF) type schemes with Galerkin finite element approximations for the time-dependent nonlinear thermistor equations. Optimal L 2 error estimates for the proposed schemes are proved unconditionally. The proof consists of two steps. First, the boundedness of the numerical solution in certain strong norms is obtained by a temporal-spatial error splitting argument. Second, a traditional approach is used to provide an optimal L 2 error estimate for r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Remark In order to bound B 5 , we estimate e n in H 1 ‐norm first and then derive e n in H 2 ‐norm. On the other hand, comparing with Liu and Gao, in order to achieve the temporal error with O ( τ 3 ) in H 2 ‐norm, we multiply by D τ e n and D τ Δ e n instead of 2 e n − e n − 1 and 2Δ e n − Δ e n − 1 , respectively. Further, we rewrite the error equation through to avoid transferring τ from one part in the inner product to the other hand.…”
Section: Fully Discrete System Concerning About Temporal‐discrete Schemementioning
confidence: 99%
See 3 more Smart Citations
“…Remark In order to bound B 5 , we estimate e n in H 1 ‐norm first and then derive e n in H 2 ‐norm. On the other hand, comparing with Liu and Gao, in order to achieve the temporal error with O ( τ 3 ) in H 2 ‐norm, we multiply by D τ e n and D τ Δ e n instead of 2 e n − e n − 1 and 2Δ e n − Δ e n − 1 , respectively. Further, we rewrite the error equation through to avoid transferring τ from one part in the inner product to the other hand.…”
Section: Fully Discrete System Concerning About Temporal‐discrete Schemementioning
confidence: 99%
“…The error unUhn is split into the temporal error u n − U n and the spatial error unUhn by a time‐discrete system with solution U n . Some original techniques, like rewriting the terms in the error equation and so on, are used to get higher order of the temporal error in H 2 ‐norm than that in Gao and Cai et al As it is shown in our paper, H 2 ‐error estimate of the temporal error is important for getting rid of the restriction of τ . It is also worth to point out that a much more general condition, where f ( u ) might not satisfy the globally condition or only locally Lipschitz continuous in u , is dealt with in the our work.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, due to the existence of nonlinearity, error analysis often requires some time-step grid ratio constraints, for example, τ = O(h d/2 ), d = 2, 3 in [3,11], τ = O(h) in [25] and τ = o(h 2 ) in [24], although numerical tests show the feasibility of the numerical methods for a large time step. To overcome this problem, an error splitting technique was proposed in [22], and then widely developed in [5,6,9,8,17,14,14,15,23].…”
mentioning
confidence: 99%